2010
DOI: 10.1161/circgenetics.109.934455
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Loci Influence Serum Urate Levels and Their Relationship With Gout and Cardiovascular Disease Risk Factors

Abstract: Background Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed genome-wide association to search for genetic susceptibility loci for serum urate and gout, and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). Methods and Results Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the CHARGE consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
296
4
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(323 citation statements)
references
References 24 publications
19
296
4
4
Order By: Relevance
“…By contrast, CORs were not significant for any of these conditions when calculated using the GRS derived from SNPs associated with UA concentration. This is in line with a meta-analysis from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, which did not find an association of a genetic urate score with incident CAD, 32 and Palmer et al, who found no association of UA with prospectively assessed ischemic heart disease in their recent MR study. 24 Because this study only used one SNP in the SLC2A9 gene as an instrumental variable, we also calculated CORs and CHRs using a single SNP in SLC2A9 (rs12498742), which is in high linkage disequilibrium with the one used by Palmer et al The COR for prevalent CAD was not significant (data not shown) and estimates for fatal events derived from this analysis were very similar compared with the results obtained for GRS 8 (Supplemental Table 6), which is expected because the SLC2A9 SNP shows by far the strongest association with UA.…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, CORs were not significant for any of these conditions when calculated using the GRS derived from SNPs associated with UA concentration. This is in line with a meta-analysis from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, which did not find an association of a genetic urate score with incident CAD, 32 and Palmer et al, who found no association of UA with prospectively assessed ischemic heart disease in their recent MR study. 24 Because this study only used one SNP in the SLC2A9 gene as an instrumental variable, we also calculated CORs and CHRs using a single SNP in SLC2A9 (rs12498742), which is in high linkage disequilibrium with the one used by Palmer et al The COR for prevalent CAD was not significant (data not shown) and estimates for fatal events derived from this analysis were very similar compared with the results obtained for GRS 8 (Supplemental Table 6), which is expected because the SLC2A9 SNP shows by far the strongest association with UA.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the results of Mendelian randomization analysis suggest that the association between urate and AKI may not be causal, although this is not definitive given overlapping 95% CIs between the risk associated with serum urate and the risk associated with urate score. The Mendelian randomization analysis is similar to previous studies that have used a genetic urate score or individual genes associated with urate levels as instrumental variables (24,(32)(33)(34). While an association between urate score and gout has been demonstrated, no association has been observed between urate genes and BP, fasting glucose, CKD, coronary artery disease, or metabolic syndrome in these studies.…”
Section: Discussionmentioning
confidence: 88%
“…Using 7533 previously genotyped European American ARIC participants, we calculated their genetic urate score based on genotyping of eight single-nucleotide polymorphisms (24). The score, which reflects the expected difference in urate concentration from an individual homozygous for major alleles at each of the eight single-nucleotide polymorphisms , ranged from 21.1 to 1.3 mg/dl and captured 6.0% of the variation in urate levels (24).…”
Section: Laboratory Measurements and Variable Definitionsmentioning
confidence: 99%
“…ABCG2, encoding a uric acid transporter, was identified to be associated with uric acid concentration and gout (Dehghan et al, 2008); its variants reduce the excretion of uric acid by the kidney. However, the genetic urate score analysis did not provide evidence for an association between serum urate and cardiovascular risk factors or coronary heart disease (Yang et al, 2010). FTO, encoding a nuclear protein of the AlkB-related non-heme iron and 2-oxoglutarate-dependent oxygenase superfamily, was identified as an obesity-related gene, and which increased obesity-related vascular diseases (Al-Attar et al, 2008).…”
Section: Discussionmentioning
confidence: 97%